Agricultural drought monitoring and management at sub district level in Telangana - REDDY, D. RAJI; SREENIVAS, G. (MAUSAM, 2016)
The weather or climate is considered as an important natural resource and basic input for better planning of crop and cropping system in agriculture particularly rainfed environments. Every plant process, related with growth, development and yield of a crop and each of in-season and off-season farm operations depends on weather. Amongst the various weather elements, temperatures, radiation and rainfall play crucial role in deciding the crop growth, development and yield levels. Precipitation is one of the important weather factors being responsible for atmospheric and soil moisture and therefore has more agricultural importance, especially in rainfed agriculture. Rainfed crops like jowar, maize, groundnut, greengram, blackgram and sunflower and one water-intensive crop like rice are mainly affected owing to drought. The drought conditions occur due to failure of South West Monsoon, delay in arrival of SW monsoon, and break monsoon conditions or early cessation of SW monsoon. Rainfed agriculture in India depends on onset of monsoon and the rainfall distribution during crop growth season. The amount of rainfall and the time of onset of monsoon decides the type of the crop to be grown. The timely onset and well distribution of monsoon rain in the month of June and July decides the area coverage of rainfed crops. Any deviation in the onset and distribution of southwest monsoon rainfall causes huge impact on agriculture and its dependent activities. Close monitoring of progress of monsoon and distribution of rainfall and its impact on sowing of rainfed crops is essential at sub district level to suggest time to time crop management strategies thereby to minimize the impact of aberrant seasonal conditions. In this paper a monitoring of drought at national, state and sub district (Mandal) level using indices like MAI, WRSI etc. were presented. Management strategies to reduce the impact of drought like optimum time of sowing, strategic irrigation, crop calendar, contingency crop planning etc. were discussed. Agromet advisories for communication of real time weather information for benefit of farming community were presented.